An RB insensitive to CDK regulation - Joaquin, Manel (Mol Cell Oncol, 2016)
The N-term phosphorylation of Retinoblastoma (RB) by the p38 stress-activated protein kinase (SAPK) makes RB insensitive to cyclin-dependent kinase (CDK)-Cyclin inhibition, which enhances the transcriptional repression of E2F-driven promoters and delays tumor cell growth. This novel mechanism of RB regulation opens up a window for developing new cancer drug treatments for tumors harboring high CDK-Cyclin activity and a wild-type RB gene.